Determinación de la disponibilidad de carbono según la tipificación de los sistemas agroforestales de café en las sub cuencas del Río Yuracyacu y Yanayacu - López López, Karen Diana (2014)
Climate change is one of the most serious environmental problems facing human beings and all forms of life existing on the planet, and one of the main causes of this phenomenon is the emission of greenhouse gases as it is the carbon dioxide (C02) is a gas that contributes most to global warming; one way to mitigate the effects of this phenomenon, it is storing this gas in the biomass, from there to the agroforestry systems represent significant carbon sinks, in this respect, the objective of this study was to determine the amount of aboveground biomass and total carbon stored in the different sources of storage of coffee agroforestry systems. The present investigation carried out in two sub basins of the High May, the Yanayacu and Yuracyacu sub basin; in Moyobamba y Rioja respectively, in them 1 O estates of coffee were selected; 04 in Yanayacu sub basin and 06 in Yuracyacu sub basin, settling in each of them a plot with a dimension of 5000m2 to perform an inventory of the treeline, the identification of the species used as shadow and within this same plot was also installed a sub plot with an area of 100m2 for its biometric evaluation and determination of carbon through allometric equations, with the implementation of this methodology as a result, we found that the availability of carbon in the agroforestry systems; "Coffee" (Coffea arabica) and treeline (lnga spp and other species) it is estimated that the 64.35 % of stored carbon is located in the treeline and the 35.65 % is available in the coffee plantations.